Study of some physical properties of bismuth doped borate glass - Ghanem, A. H.; Gaballah, N. (IJRDO-Journal of Applied Science, 2016)
Glass samples of the formula (70-x) B2O3 -xBi2O3-15Zn-15Na2O havebeen prepared by the melting quenching technique. The structural andoptical characterisations of the glassy system were carried out by XRD,density, molar volume and FTIR technique. The powder X- ray diffractionof the prepared glass confirms the amorphous nature. FTIR analysisindicates dependence of the number of structural units of BO3 and BO4 onBi2O3 concentration. It is assumed that Bi2O3 enters the structure in theform of BiO6. Bi2O3 in different structural units like tri, tetra, penta andoctahedral groups are confirmed in the glass matrix. The change ofdensity, molar volume and N4 ratio with Bi2O3 content confirm thetransformation of structural units of BO3 into BO4 by Bi2O3 addition